Back Cover: Compact, Polyvalent Mannose Quantum Dots as Sensitive, Ratiometric FRET Probes for Multivalent Protein–Ligand Interactions (Angew. Chem. Int. Ed. 15/2016). Issue 15 (16th March 2016) - Guo, Yuan; Sakonsinsiri, Chadamas; Nehlmeier, Inga; Fascione, Martin A.; Zhang, Haiyan; Wang, Weili; Pöhlmann, Stefan; Turnbull, W. Bruce; Zhou, Dejian
Abstract : Four bees, mimicking the four carbohydrate‐recognition domains (CDRs) in the HIV/Ebola receptor DC‐SIGN, are searching for "lollipops", that is, polyvalent carbohydrate‐conjugated quantum dots (QDs). To succeed, they have to follow the right "SIGN", fly in the same direction, and work together. In their Communication onpage 4738 ff., Y. Guo, D. Zhou et al. report on the simultaneous binding of four CRDs in DC‐SIGN with a polyvalent QD to achieve high‐affinity binding.